DE PASTORES A FEITICEIROS: A HISTORIOGRAFIA DO PROTESTANTISMO BRASILEIRO (1950-1990) - Watanabe, Tiago Hideo Barbosa (2006)
The present work had as study object the Brazilian protestant historiography, especially presbyterian, of the decades of 1950 until the beginning of 1990. The visualization of the dispute around representations in this historiography showed a dynamic of the production place, in which a simple dualist clivagem (between pursued and persecuting) is not enough for the understanding of the many interests and there involved agents. The great occurred transformations in the Brazilian religious institutions during this period had affected in differentiated way the concretely protestant historiography and citizens. From a critical one based in some estimated of New Cultural History, we visualize that the historiography constructed the protestantism from definitive problems, relations and characters which, unmixedly exclude other citizens and subjects. An interpretative project of little problematization of documents of the institutional machine was consolidated; it neglects aspects of the Brazilian religious culture, of the operationalization of the hair power and the capacity of the citizens to re-significated imposed practical speeches and